Catalytic electrode, catalytic electrode preparation method and NO sensor

By using proton conductor layers and nano-scale precious metal layers to form a columnar ordered array structure in the catalytic electrode of the NO sensor, the problem that existing NO sensors are difficult to identify extremely trace NO gases is solved, and high sensitivity and rapid response effects are achieved.

CN119780187APending Publication Date: 2025-04-08SHENZHEN MEIHAO CHUANGYI MEDICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411937305.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing NO sensors are difficult to identify extremely trace amounts of NO gas exhaled by the human body, and it is necessary to improve the catalytic efficiency of the catalytic electrode to improve detection sensitivity.

Method used

By using a proton conductor layer and a nano-scale precious metal layer in the catalytic electrode, a columnar ordered array structure is formed to improve the specific surface area and reaction sites, thereby improving the catalytic efficiency.

Benefits of technology

The efficient catalysis of the catalytic electrode is achieved, the sensitivity and response speed of the NO sensor are improved, the amount of precious metals is reduced, and the problem of carbon materials forming hydrogen peroxide in the acidic electrolyte system is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119780187A_ABST
    Figure CN119780187A_ABST
Patent Text Reader

Abstract

The present application relates to a catalytic electrode, a method for preparing the catalytic electrode and an NO sensor, wherein the catalytic electrode comprises a gas permeable substrate and a catalytic layer, the catalytic layer comprises a proton conductor layer and a nanometer-scale precious metal layer, the proton conductor layer has a columnar ordered array structure, and the nanometer-scale precious metal layer is deposited on the columnar ordered array structure. In the sensor assembled by using the catalytic electrode of the present application, because the ordered structure of the proton conductor layer is conducive to material transport, proton conduction and electron conduction, more three-phase reaction interfaces can be formed, thereby improving the sensitivity and response speed of the sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of gas sensors, and in particular to a catalytic electrode, a method for preparing the catalytic electrode, and a NO sensor. Background Art

[0002] Human exhaled breath mainly includes nitrogen, oxygen, carbon dioxide, water vapor, inert gases and thousands of trace volatile organic compounds (VOCs) and inorganic molecules (such as NO, NH3 and CO, etc.). Nearly 3,500 volatile organic compounds have been identified in human exhaled breath. They are the products of metabolism, decomposition and exogenous exposure processes that occur continuously in the human body. Most substances are exogenous and come from inhalation of environmental pollutants, food intake, skin contact and drug metabolism, etc., which can reflect the impact of external factors on human health.

[0003] The metabolites VOCs that are excreted from the body through exhaled breath and come from physiological and pathological reactions of the human body contain rich biological characteristics information. Breathing can be used as a medium for metabolomics. Respiratory metabolomics can provide an in-depth understanding of all metabolic processes in the human body and provide more comprehensive information on physical condition. Exhaled breath analysis can detect metabolites in human exhaled breath and monitor their changes, which can be used to assess the health status of the human body and diagnose diseases.

[0004] At present, the exhaled breath molecular diagnostic products such as inflammation meters developed and produced based on NO sensors can detect NO gas signal molecules in exhaled breath and monitor their changes, and are used to evaluate and monitor the development of diseases. At the same time, inflammation meter products based on NO breath detection are entering a high-speed growth period from the incubation period, and have covered more than half of the country's tertiary hospitals, and are widely used in clinical routine examinations in respiratory disease outpatient clinics and wards.

[0005] However, to identify extremely small amounts of NO gas (normal human exhaled NO < 25ppb) from the thousands of gases exhaled by the human body, the NO sensor is required to have extremely high sensitivity to NO gas. Usually, the catalytic efficiency of the catalytic electrode is improved to improve the detection sensitivity of the NO sensor to NO gas. Summary of the invention

[0006] One of the purposes of the present application is to provide a catalytic electrode that can form a larger specific surface area, thereby providing more reaction sites and further improving its catalytic efficiency.

[0007] The second purpose of the present application is to provide a method for preparing a catalytic electrode. The catalytic electrode prepared by the preparation method can form a larger specific surface area, thereby providing more reaction sites, so that the catalytic electrode has the advantage of high catalytic efficiency.

[0008] The third object of the present application is to provide a NO sensor, wherein the counter electrode adopts the catalytic electrode of one of the above objects. Since the catalytic electrode adopted has high catalytic efficiency, the NO sensor has the advantage of high sensitivity.

[0009] One of the purposes of this application is to adopt the following technical solution:

[0010] A catalytic electrode comprises a gas permeable substrate and a catalytic layer, wherein the catalytic layer comprises a proton conductor layer and a nanometer-scale noble metal layer, wherein the proton conductor layer has a columnar ordered array structure, and the nanometer-scale noble metal layer is deposited on the columnar ordered array structure.

[0011] By adopting the above technical scheme, the ordered structure of the proton conductor layer is conducive to material transport, proton conduction and electron conduction. Compared with the disordered holes of the traditional coating structure, the pathways formed by the ordered structure are easy for gas diffusion and transmission, making the path and resistance of the gas to reach the reaction interface smaller, thereby improving the efficiency of the catalytic electrode participating in the reaction; at the same time, the ordered structure is more conducive to the loading of precious metals, forming a larger specific surface area, providing more reaction sites, and thus improving the catalytic efficiency; in addition, in specific applications, the proton conductor serves as a supporting structure of the ordered structure, which is conducive to the protons generated by the electrochemical reaction being transferred to the electrolyte through the ordered structure.

[0012] Furthermore, the column height in the columnar ordered array structure is 2μm±10%, and the spacing between adjacent columns is 400nm±10%; and / or, the columnar ordered array structure is a cylindrical array structure, and the diameter of the columns in the cylindrical array structure is 200nm±10%.

[0013] Furthermore, the catalytic electrode also includes a modifier disposed on the surface of the nano-scale noble metal layer, and the modifier is metal porphyrin.

[0014] The second purpose of this application adopts the following technical solution:

[0015] A method for preparing a catalytic electrode comprises the following steps:

[0016] Providing a pre-treated substrate; wherein the pre-treated substrate comprises a base layer, a photoresist spacer layer and a proton conductor layer;

[0017] Exposure and development treatment, spin coating photoresist on the surface of the proton conductor layer of the pretreated substrate, pre-baking treatment, exposure and development using a mask, forming a protective pattern of the photoresist on the surface of the proton conductor layer to obtain a substrate to be etched; wherein the protective pattern corresponds to the mask pattern of the mask;

[0018] Etching treatment, using a deep reactive ion etching process to etch the substrate to be etched, and etching the proton conductor layer to form a columnar ordered array structure; wherein the arrangement pattern of the columnar ordered array structure corresponds to the protection pattern;

[0019] Transfer processing, transferring the columnar ordered array structure to a gas permeable substrate to obtain an electrode substrate;

[0020] Deposition treatment, depositing a noble metal material on the surface of the columnar ordered array structure of the electrode substrate, and annealing treatment to form a nano-scale noble metal layer;

[0021] Obtain the target electrode.

[0022] By adopting the above technical scheme, a proton conductor layer with a columnar ordered array structure is formed on the surface of the breathable film, and a nano-scale precious metal layer is deposited on the surface of the proton conductor layer to prepare a target electrode with good electronic conductor and catalytic activity; compared with the disordered holes of the traditional coating structure, the passages formed by the ordered structure are easy for gas diffusion and transmission, so that the path and resistance of the gas to the reaction interface are smaller, thereby improving the efficiency of the catalytic electrode participating in the reaction; at the same time, the ordered structure is more conducive to the loading of precious metals, forming a larger specific surface area, providing more reaction sites, and thus improving the catalytic efficiency; in addition, in specific applications, the proton conductor serves as a supporting structure of the ordered structure, which is conducive to the protons generated by the electrochemical reaction being transferred to the electrolyte through the ordered structure. On the other hand, the target electrode is prepared by semiconductor process technology, and its process controllability and batch consistency are more guaranteed than the traditional slurry coating process, and the use of deposition to form the catalytic layer can reduce the use of precious metals, thereby helping to form a cost advantage; and the use of proton conductors as carriers in this technical solution also avoids the use of carbon materials, so that in sensors assembled with target electrodes, it is possible to avoid the formation of excessive background current due to the formation of hydrogen peroxide by carbon materials in an acidic electrolyte system, thereby improving the stability of the sensor.

[0023] Furthermore, the proton conductor layer includes an electrostatically active material and a proton conductor.

[0024] By adopting the above technical solution, when etching is performed in the deep reactive ion etching process, the plasma will bombard the proton conductor layer so that charged particles are formed on the surface of the proton conductor layer and then an electrostatic field is formed; by configuring electrostatically active substances in the proton conductor layer, the electrostatic field can be maintained for a longer time, so that the columnar ordered array structure formed by the proton conductor layer can maintain its shape without collapsing, thereby maintaining the stability of the columnar ordered array structure during the preparation process.

[0025] Furthermore, the electrostatically active substance is one or more of polyethoxylated stearyl alcohol, polyalkylene glycol, polyalkylene ether, quaternary ammonium salt or ammonium halide salt.

[0026] Furthermore, the proton conductor is a polymer proton conductor, and the polymer proton conductor is perfluorosulfonic acid.

[0027] Furthermore, the column height in the columnar ordered array structure is 2μm±10%, and the spacing between adjacent columns is 400nm±10%; and / or, the columnar ordered array structure is a cylindrical array structure, and the diameter of the columns in the cylindrical array structure is 200nm±10%.

[0028] Furthermore, in the deposition step, the precious metal material is platinum, a binary alloy of platinum or a ternary alloy of platinum, the deposition thickness is 100-500 nm, and the annealing temperature is 200-300°C.

[0029] Furthermore, after the deposition treatment step, the method further includes: coating a modifier, spraying an electrode modification solution on the surface of the nano-scale noble metal layer, and drying the electrode modification solution; wherein the electrode modification solution includes a transition metal compound.

[0030] By adopting the above technical solution, NO is a typical coordination molecule with good coordination and complexing ability with transition metals. By using transition metal compounds as electrode modifiers, such electrode modifiers can act as electron mediators in the electrochemical oxidation process of NO, thereby improving the sensitivity of the NO electrochemical sensor assembled using the target electrode.

[0031] Furthermore, the step of providing a pre-treated substrate specifically includes the following steps:

[0032] Removing organic matter, inorganic particles and metal ions on the surface of the substrate;

[0033] Spin-coating photoresist on the base layer, exposing and curing, to obtain a first substrate; wherein the photoresist is cured to form the photoresist interlayer;

[0034] The proton conductor solution is spin-coated on the surface of the first substrate and dried to obtain a pretreated substrate; wherein the proton conductor solution includes Nafion TM A polymer dispersant, a polyalkylene ether and an electrostatic activator are added, and the proton conductor solution is dried to form the proton conductor layer.

[0035] The third purpose of this application adopts the following technical solution:

[0036] A NO sensor comprises a counter electrode, a working electrode and a reference electrode capable of constructing a three-electrode system in an electrolyte, wherein the counter electrode is a target electrode obtained by the above-mentioned catalytic electrode preparation method.

[0037] By adopting the above technical solution, the ordered structure of the proton conductor layer is conducive to material transport, proton conduction and electron conduction, and more three-phase reaction interfaces can be formed, which can improve the sensitivity and response speed of the sensor.

[0038] In summary, this application at least includes the following beneficial technical effects:

[0039] The ordered structure of the proton conductor layer is conducive to material transport, proton conduction and electron conduction. Compared with the disordered holes in the traditional coating structure, the pathways formed by the ordered structure are easy for gas diffusion and transmission, making the path and resistance of the gas to the reaction interface smaller, thereby improving the efficiency of the catalytic electrode participating in the reaction; at the same time, the ordered structure is more conducive to the loading of precious metals, forming a larger specific surface area, providing more reaction sites, and thus improving the catalytic efficiency; in addition, in specific applications, the proton conductor serves as a supporting structure for the ordered structure, which is conducive to the protons generated by the electrochemical reaction being transferred to the electrolyte through the ordered structure.

[0040] At the same time, the semiconductor process technology is used to prepare the catalytic electrode, and its process controllability and batch consistency are more guaranteed than the traditional slurry coating process, and the deposition method to form the catalytic layer can reduce the use of precious metals, thereby helping to form a cost advantage; and the use of proton conductors as carriers in the present technical solution also avoids the use of carbon materials, so that in the sensor assembled with the catalytic electrode, it can avoid the carbon material forming hydrogen peroxide in the acidic electrolyte system and causing excessive background current, thereby improving the stability of the sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a schematic diagram used to illustrate some steps in the method for preparing a catalytic electrode in the embodiment of the present application;

[0042] Figure 2 It is a microscopic enlarged schematic diagram used to demonstrate the columnar ordered array formed by the proton conductor layer containing electrostatically active substances under etching treatment in the embodiment of the present application;

[0043] Figure 3 It is a microscopic enlarged schematic diagram used to demonstrate the columnar ordered array formed by the proton conductor layer without electrostatic active substances after re-etching treatment in the embodiment of the present application. DETAILED DESCRIPTION

[0044] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0045] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "axial", "radial", "circumferential" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more.

[0046] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0047] The embodiment of the present application discloses a method for preparing a catalytic electrode. The catalytic electrode prepared by the preparation method can form a larger specific surface area, thereby providing more reaction sites, so that the catalytic electrode has the advantage of high catalytic efficiency. If the catalytic electrode is used to assemble an NO sensor, the sensitivity of the NO sensor can be improved.

[0048] Refer to the attached Figure 1 In a specific embodiment, the method for preparing a catalytic electrode includes the following steps.

[0049] S01. Providing a pre-treated substrate.

[0050] The pre-treated substrate specifically includes a base layer, a photoresist spacer and a proton conductor layer which are arranged in sequence.

[0051] In some specific examples, the base layer is made of a silicon wafer, and the photoresist spacer is formed by curing a negative photoresist.

[0052] In some embodiments, the proton conductor layer includes an electrostatically active substance and a proton conductor. Accordingly, in some specific examples, the electrostatically active substance is one or more of polyethoxylated stearyl alcohol, polyalkylene glycol, polyalkylene ether, quaternary ammonium salt or halide ammonium salt. In some specific examples, the proton conductor is a polymer proton conductor, and specifically in this embodiment, the polymer proton conductor is perfluorosulfonic acid.

[0053] It should be noted that, in step S01, a prefabricated pretreated substrate can be directly used, or the pretreated substrate can be prepared on site. Accordingly, the specific steps of preparing the pretreated substrate are described in detail below.

[0054] S02: exposure and development processing.

[0055] Spin-coat photoresist on the surface of the proton conductor layer at a spin-coating speed of 1000-3000 rpm, and then pre-bake for 10 minutes on a hot plate at 80-90°C. Use a mask to perform exposure and development, and form a protective pattern on the photoresist on the surface of the proton conductor layer to obtain a substrate to be etched.

[0056] The photoresist spin-coated in step S02 is a negative photoresist, specifically Microchem SU-8 photoresist is used in this embodiment; meanwhile, the protection pattern corresponds to the mask pattern of the mask plate.

[0057] It should be noted that the mask used in this solution can selectively transmit ultraviolet light. Specifically, a mask pattern that allows ultraviolet light to pass through is set on the mask, while the mask area outside the mask pattern cannot transmit ultraviolet light.

[0058] Accordingly, in the process of exposure and development using a mask, the mask is first aligned with the pre-treated substrate, and ultraviolet light is used to irradiate the area of ​​the photoresist that is exposed to the ultraviolet light so that the area is cured, and the pattern of this part of the cured area corresponds to the mask pattern. After the exposure is completed, the hardened film is baked at 120°C for 30 to 60 minutes, and then a developer is used to dissolve the unexposed and cured area on the photoresist, so that the exposed and cured area on the photoresist is retained to form a protective pattern corresponding to the mask pattern.

[0059] S03: etching process.

[0060] The substrate to be etched is etched by using a deep reactive ion etching process, and a columnar ordered array structure is formed in the proton conductor layer; wherein the arrangement pattern of the columnar ordered array structure corresponds to the protection pattern.

[0061] Among them, the deep reactive ion etching process is a mature microelectronic dry etching process, which is mainly used for etching micro-nano structures such as silicon, SOI, silicon oxide, and silicon nitride. Among them, silicon etching is divided into two processes, Bosch and Mix-gas, which can respectively achieve high aspect ratio etching and nanostructure shallow etching. Specifically, the Bosch etching process is used in this embodiment to achieve high aspect ratio etching.

[0062] It should be noted that during the etching process, the proton conductor layer not covered by the protective pattern is corroded, while the proton conductor layer covered by the protective pattern is retained, thereby forming a columnar ordered array structure corresponding to the protective pattern.

[0063] Reference Figure 2 , which shows a microscopic diagram of a columnar ordered array formed by the proton conductor layer containing electrostatically active substances during the etching process in step S03, compared with Figure 3 , which shows a microscopic enlarged schematic diagram of a columnar ordered array formed by a proton conductor layer containing no electrostatically active substances after etching treatment in step S03; by comparison, it can be seen that the columnar ordered array structure formed by the proton conductor layer containing electrostatically active substances after etching treatment can maintain its shape without collapsing.

[0064] In some specific embodiments, the height of the pillars in the pillar-shaped ordered array structure is 2 μm±10%, and the spacing between adjacent pillars is 400 nm±10%.

[0065] In some more specific embodiments, the columnar ordered array structure is configured as a cylindrical array structure, and the diameter of the columns in the cylindrical array structure is 200 nm±10%.

[0066] S04: transfer processing.

[0067] The columnar ordered array structure is transferred to a gas permeable substrate to obtain an electrode substrate.

[0068] In some specific examples, step S04 specifically includes the following steps.

[0069] S041, using a degumming liquid to remove the residual photoresist on the surface of the columnar ordered array structure, wherein the residual photoresist is the photoresist solidified area forming the protective pattern.

[0070] S042, thermally transferring the product of step S041 to a breathable substrate at a transfer temperature of 120°C and a pressure of 1.5 kg / cm2. In some specific examples, the breathable substrate may be a polytetrafluoroethylene film.

[0071] S043, using a degumming solution to remove the photoresist interlayer and the base layer, thereby obtaining an electrode substrate having a columnar ordered array structure supported on a gas permeable substrate.

[0072] S05: deposition treatment.

[0073] A noble metal material is deposited on the surface of the columnar ordered array structure of the electrode substrate, and annealing is performed to form a nanometer-scale noble metal layer.

[0074] In some embodiments, the noble metal material is platinum, a binary alloy of platinum, or a ternary alloy of platinum, the deposition thickness is 100-500 nm, and the annealing temperature is 200-300° C.

[0075] Specifically in this embodiment, the precious metal material is platinum, and the atomic layer deposition process is specifically used to deposit a platinum layer with a thickness of 200nm on the surface of the columnar ordered array structure, and annealing is performed at 220°C for 6 to 8 hours. The atomic layer deposition process has a good step coverage rate, which can make the platinum layer form a continuous electronic conductor layer on the surface of the columnar ordered array structure, thereby reducing the surface resistance of the nano-scale precious metal layer.

[0076] In other embodiments, the precious metal material is platinum, and a platinum layer with a thickness of 100 nm is deposited on the surface of the columnar ordered array structure, and annealing is performed at 200°C for 6 to 8 hours. In other embodiments, the precious metal material is platinum, and a platinum layer with a thickness of 400 nm is deposited on the surface of the columnar ordered array structure, and annealing is performed at 250°C for 6 to 8 hours. In other embodiments, the precious metal material is platinum, and a platinum layer with a thickness of 500 nm is deposited on the surface of the columnar ordered array structure, and annealing is performed at 300°C for 6 to 8 hours.

[0077] At the same time, in some other embodiments, the precious metal material is platinum palladium, and a platinum palladium layer with a thickness of 200 nm is deposited on the surface of the columnar ordered array structure; in some other embodiments, the precious metal material is platinum ruthenium, and a platinum ruthenium layer with a thickness of 200 nm is deposited on the surface of the columnar ordered array structure.

[0078] S06. Obtain target electrodes.

[0079] By adopting the above-mentioned preparation process, a proton conductor layer with a columnar ordered array structure can be formed on the surface of the breathable film, and a nano-scale precious metal layer is deposited on the surface of the proton conductor layer to prepare a target electrode with good electronic conductor and catalytic activity; compared with the disordered holes of the traditional coating structure, the passage formed by the ordered structure is easy for gas diffusion and transmission, so that the path and resistance of the gas to the reaction interface are smaller, thereby improving the efficiency of the catalytic electrode participating in the reaction; at the same time, the ordered structure is more conducive to the loading of precious metals, forming a larger specific surface area, providing more reaction sites, and thus improving the catalytic efficiency; in addition, in specific applications, the proton conductor serves as a supporting structure of the ordered structure, which is conducive to the protons generated by the electrochemical reaction being transferred to the electrolyte through the ordered structure. And when etching is performed in the deep reactive ion etching process, the plasma will bombard the proton conductor layer, so that charged particles are formed on the surface of the proton conductor layer, thereby forming an electrostatic field; by configuring the electrostatic active material on the proton conductor layer, the electrostatic field can be maintained for a longer time, so that the columnar ordered array structure formed by the proton conductor layer can maintain its shape without collapse, and maintain the stability of the columnar ordered array structure during the preparation process.

[0080] Furthermore, in some embodiments, the following steps are also included after step S05:

[0081] S055, coating modifier.

[0082] The electrode modification solution is sprayed on the surface of the nano-scale precious metal layer and then dried.

[0083] The electrode modification solution includes a transition metal compound, and the electrode modification solution forms a modifier on the electrode surface after being dried.

[0084] Since NO is a typical coordination molecule with good coordination and complexing ability with transition metals, by using transition metal compounds as electrode modifiers, such electrode modifiers can act as electron mediators in the electrochemical oxidation process of NO, thereby improving the sensitivity of the NO electrochemical sensor assembled using the target electrode.

[0085] Furthermore, in some specific examples, the metal porphyrin solution is a solution prepared by dissolving iron porphyrin in a polar solvent of dimethyl sulfoxide; after the electrode modification solution is sprayed on the surface of the nano-scale noble metal layer, it is dried at 120° C. for 2 hours.

[0086] In some specific examples, the process of preparing the pre-treated substrate in the above step S01 includes the following steps.

[0087] S011. Clean the base layer to remove organic matter, inorganic particles and metal ions on the surface of the base layer.

[0088] Among them, the base layer is a silicon wafer.

[0089] In some specific examples, the method for removing organic matter on the surface of the substrate layer is as follows: adding 98% sulfuric acid and 30% hydrogen peroxide solution by volume in an ultrasonic cleaning tank in a ratio of 4:1, controlling the temperature of the cleaning tank at 120-150°C, and removing the organic matter on the surface of the substrate layer by ultrasonic cleaning.

[0090] In some specific examples, the method for removing inorganic particles on the surface of the substrate layer is as follows: adding ammonia water, hydrogen peroxide and ultrapure water into another ultrasonic cleaning tank, preferably in a ratio of 1:4:25, controlling the temperature of the ultrasonic cleaning tank at 70-90°C, and removing the inorganic particles on the surface of the substrate layer by ultrasonic cleaning.

[0091] In some specific examples, the method for removing metal ion substances on the surface of the substrate layer is as follows: hydrochloric acid, hydrogen peroxide and ultrapure water are added to another ultrasonic cleaning tank, and the ratio is preferably 1:1:6, the pH value of the solution is controlled between 2.5 and 6, the temperature of the ultrasonic cleaning tank is controlled at 70 to 90°C, and ultrasonic cleaning is performed to remove the metal ions on the surface of the substrate layer.

[0092] S012. Obtain a first substrate.

[0093] The base layer is spin-coated with a photoresist having a thickness of 0.5 to 2 μm, and the spin-coating speed is set to 1000 to 3000 rpm. The base layer is then pre-baked at 80 to 90° C. for 10 minutes using a hot plate, and the photoresist is cured by exposure using a photolithography machine to obtain a first substrate.

[0094] The photoresist is cured to form a photoresist spacer.

[0095] S013, obtaining a pretreated substrate.

[0096] The proton conductor solution is spin-coated on the surface of the first substrate and dried to obtain a pre-treated substrate; wherein the proton conductor solution includes Nafion TM A polymer dispersant, a polyalkylene ether and an electrostatic activator are added, and the proton conductor solution is dried to form a proton conductor layer.

[0097] In some specific embodiments, the polymer dispersant is selected from Nafion TM The polymer dispersant is of grade D2020CS, and the content of polyalkylene ether in the solution is 0.5%wt; the electrostatic activator is one or more of polyethoxylated stearyl alcohol, polyalkylene glycol, polyalkylene ether, quaternary ammonium salt or halide ammonium salt, and the proportion of the electrostatic activator in the solution is 0.01-20%.

[0098] The embodiment of the present application also discloses a catalytic electrode, which includes a breathable substrate and a catalytic layer, wherein the catalytic layer includes a proton conductor layer and a nano-scale precious metal layer, and the proton conductor layer has a columnar ordered array structure, and the nano-scale precious metal layer is deposited on the columnar ordered array structure. In some embodiments, the proton conductor layer in the catalytic layer is adhered to the breathable substrate by thermal transfer, and the nano-scale precious metal layer is attached to the columnar ordered array structure of the proton conductor layer by deposition, so as to achieve the coordination of the catalytic layer and the breathable substrate; in other embodiments, other existing methods can also be used to achieve the coordination of the catalytic layer and the breathable substrate. In some specific examples, the breathable substrate is made of polytetrafluoroethylene, and the nano-scale precious metal layer is a nano-scale platinum layer formed by deposition.

[0099] In some embodiments, the height of pillars in the pillar-shaped ordered array structure is 2 μm±10%, and the spacing between adjacent pillars is 400 nm±10%.

[0100] In some more specific embodiments, the columnar ordered array structure is configured as a cylindrical array structure, and the diameter of the columns in the cylindrical array structure is 200 nm±10%.

[0101] Furthermore, in some embodiments, the catalytic electrode also includes a modifier formed by metal porphyrin. In this embodiment, the modifier is iron porphyrin. The ordered structure of the proton conductor layer in the above-mentioned catalytic electrode is conducive to material transport, proton conduction and electron conduction. Compared with the disordered holes in the traditional coating structure, the passage formed by the ordered structure is easy for gas diffusion and transmission, so that the path and resistance of the gas to the reaction interface are smaller, thereby improving the efficiency of the catalytic electrode participating in the reaction; at the same time, the ordered structure is more conducive to the loading of precious metals, forming a larger specific surface area, providing more reaction sites, and thus improving the catalytic efficiency; in addition, in specific applications, it is conducive to the proton conductor as a supporting structure of the ordered structure, and the protons generated by the electrochemical reaction are transferred to the electrolyte through the ordered structure.

[0102] In addition, the catalytic electrode of this embodiment can be prepared by using the catalytic electrode preparation method described above.

[0103] The embodiment of the present application also discloses a NO sensor, which includes a shell, an electrolyte, a glass fiber, three pins, and a counter electrode, a working electrode and a reference electrode that can construct a three-electrode system in the electrolyte, wherein the counter electrode adopts the above-mentioned catalytic electrode; at the same time, the glass fiber is used to adsorb the electrolyte and form a closed loop, and the glass fiber also separates the counter electrode, the reference electrode and the working electrode; in addition, the three pins all extend from the inside of the shell to the outside of the shell, and the three pins are connected to the counter electrode, the reference electrode and the working electrode one by one.

[0104] Accordingly, some specific examples and comparative examples of NO sensors are provided below.

[0105] Example 1

[0106] The NO sensor of this example includes a housing, an electrolyte, glass fiber, three pins, and a counter electrode, a working electrode, and a reference electrode capable of constructing a three-electrode system in the electrolyte, wherein the counter electrode adopts the aforementioned catalytic electrode, and the catalytic electrode can be prepared by the aforementioned catalytic electrode preparation method; and the catalytic electrode includes a permeable substrate, a catalytic layer, and a modifier arranged in sequence, wherein the permeable substrate adopts a polytetrafluoroethylene film, the catalytic layer includes a nano-scale platinum layer deposited on the aforementioned proton conductor layer and the columnar ordered array structure of the proton conductor layer, and the modifier adopts iron porphyrin. At the same time, the electrolyte adopts a sulfuric acid electrolyte with a mass fraction of 40%, the pins adopt gold-plated acid-resistant stainless steel pins, and the working electrode and the reference electrode both adopt graphite electrodes.

[0107] Comparative Example 1

[0108] The NO sensor of this example includes a shell, an electrolyte, glass fiber, three pins, and a counter electrode, a working electrode and a reference electrode that can construct a three-electrode system in the electrolyte, wherein the counter electrode adopts a platinum-carbon electrode, which is prepared by a conventional silk-screen printing process, and iron porphyrin is provided on the platinum-carbon electrode as a modifier; at the same time, the electrolyte adopts a sulfuric acid electrolyte with a mass fraction of 40%, the pins adopt gold-plated acid-resistant stainless steel pins, and the working electrode and the reference electrode both adopt graphite electrodes.

[0109] Specifically, the preparation method of the aforementioned platinum-carbon electrode is: screen printing the conductive paste onto the hydrophobic breathable membrane, drying it, and obtaining the platinum-carbon electrode. The conductive paste includes precious metal nanomaterials, carbon materials, and adhesive materials with a solid content ratio of 4:5:1, wherein the precious metal nanomaterial is precious metal platinum, the carbon material is graphite, and the adhesive material is polyurethane; meanwhile, the hydrophobic breathable membrane is a polytetrafluoroethylene film.

[0110] The NO sensors of Example 1 and Comparative Example 1 were subjected to aging treatment and then performance tests were performed.

[0111] Aging treatment: Place the sensor on a +0.35mV bias voltage circuit board in a normal indoor environment for 7 to 15 days to complete the polarization of the electrode sheet and the overall aging of the sensor.

[0112] The aged sensor is then installed on the sensor test fixture and the following performance test is performed.

[0113] NO response test: 2000ppb NO gas was introduced, and the ventilation rate was controlled at 100-300ccm to obtain the NO response curve of the sensor. The sensitivity and response time data of the sensor were obtained through the NO response curve of the sensor.

[0114] Interference gas cross test: 100% N2, 1.12% CO2, and 45ppm CO were introduced respectively to obtain the response current of the sensor. The response value of each interfering gas was obtained by the ratio of the response current value to the sensor sensitivity.

[0115] Cyclic test: At a fixed frequency, NO gas is introduced once every 2 minutes. The test is continued until NO gas is introduced 3000 times. The current data of the sensor in the cyclic test can be obtained. The sensitivity data of each time can be obtained through the current data of each time. The 3000 sets of sensitivity data are statistically analyzed, and the coefficient of variation is calculated by the ratio of the standard deviation to the average value. Among them, the smaller the coefficient of variation, the better the repeatability of the sensor in the cyclic test.

[0116] The performance test data of the NO sensors in Example 1 and Comparative Example 1 are summarized in the following table:

[0117]

[0118] Some of the terms involved in the above performance tests are further explained as follows:

[0119] 1. Sensitivity: The sensitivity of a sensor refers to its ability to respond to an input signal, usually expressed as the ratio between the change in the output signal and the change in the input signal. Sensitivity reflects the sensor's ability to detect small changes and is one of the important parameters for measuring its performance. Among them, the definition of electrochemical sensor sensitivity generally refers to the ratio between the sensor's current response value to the target gas and the gas concentration.

[0120] The formula is: S = ΔY / ΔX, where: S is the sensitivity; ΔY is the change in the sensor output signal (current in the above performance test); ΔX is the change in the input signal (gas concentration in the above performance test).

[0121] 2. Response time: Response time (T90) is one of the important parameters to describe sensor performance. It is used to indicate the time required for the output to reach 90% of the final stable value when the input value of the sensor changes suddenly. If the final stable value is V final , the initial value is V initial , then T90 is the time point when the output signal V(t) satisfies the following condition: V(t) = V initial +0.9×(V final -V initial ).

[0122] Through performance testing, it can be learned that since the ordered electrode structure brings more three-phase reaction interfaces, it is more conducive to gas diffusion, material transport, electron and proton conduction, so that the NO sensor of Example 1 is superior to the sensor assembled with platinum carbon electrodes prepared by conventional coating process in Comparative Example 1 in terms of sensitivity, response speed, anti-interference ability and long-term stability.

[0123] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A catalytic electrode comprising a gas permeable substrate and a catalytic layer, characterized in that: The catalytic layer comprises a proton conductor layer and a nanometer-scale noble metal layer. The proton conductor layer has a columnar ordered array structure, and the nanometer-scale noble metal layer is deposited on the columnar ordered array structure.

2. The catalytic electrode according to claim 1, characterized in that The column height in the columnar ordered array structure is 2 μm±10%, and the spacing between adjacent columns is 400 nm±10%; and / or, the columnar ordered array structure is a cylindrical array structure, and the column diameter in the cylindrical array structure is 200 nm±10%.

3. The catalytic electrode according to claim 1, characterized in that The catalytic electrode also includes a modifier arranged on the surface of the nano-scale noble metal layer, and the modifier is metal porphyrin.

4. A method for preparing a catalytic electrode, characterized in that: The following steps are involved: Providing a pre-treated substrate; wherein the pre-treated substrate comprises a base layer, a photoresist spacer layer and a proton conductor layer; Exposure and development treatment, spin coating photoresist on the surface of the proton conductor layer of the pretreated substrate, pre-baking treatment, exposure and development using a mask, forming a protective pattern of the photoresist on the surface of the proton conductor layer to obtain a substrate to be etched; wherein the protective pattern corresponds to the mask pattern of the mask; Etching treatment, using a deep reactive ion etching process to etch the substrate to be etched, and etching the proton conductor layer to form a columnar ordered array structure; wherein the arrangement pattern of the columnar ordered array structure corresponds to the protection pattern; Transfer processing, transferring the columnar ordered array structure to a gas permeable substrate to obtain an electrode substrate; Deposition treatment, depositing a noble metal material on the surface of the columnar ordered array structure of the electrode substrate, and annealing treatment to form a nano-scale noble metal layer; Obtain the target electrode.

5. The method for preparing a catalytic electrode according to claim 4, characterized in that: The proton conductor layer includes an electrostatically active material and a proton conductor.

6. The method for preparing a catalytic electrode according to claim 5, characterized in that: The electrostatic active material is one or more of polyethoxylated stearyl alcohol, polyalkylene glycol, polyalkylene ether, quaternary ammonium salt or halide ammonium salt.

7. The method for preparing a catalytic electrode according to claim 5, characterized in that: The proton conductor is a polymer proton conductor, and the polymer proton conductor is perfluorosulfonic acid.

8. The method for preparing a catalytic electrode according to claim 4, characterized in that: In the deposition step, the precious metal material is platinum, a binary alloy of platinum or a ternary alloy of platinum, the deposition thickness is 100-500 nm, and the annealing temperature is 200-300° C.

9. The method for preparing a catalytic electrode according to claim 4, characterized in that: After the deposition treatment step, the method further includes: coating a modifier, spraying an electrode modification solution on the surface of the nano-scale noble metal layer, and drying the electrode modification solution; wherein the electrode modification solution includes a transition metal compound.

10. A NO sensor, characterized in that: The invention comprises a counter electrode, a working electrode and a reference electrode which can construct a three-electrode system in an electrolyte, wherein the counter electrode adopts the catalytic electrode as claimed in any one of claims 1 to 3.